The Need for Integrative Computational Oncology: An Illustrated Example through MMP-Mediated Tissue Degradation - Mumenthaler, Shannon; D'Antonio, Gianluca; Preziosi, Luigi; Macklin, Paul (Frontiers in Oncology, 2013)
Physical oncology is a growing force in cancer research, and it is enhanced by integrative computational oncology: the fusion of novel experiments with mathematical and computational modeling. Computational models must be assessed with accurate numerical methods on correctly scaled tissues to avoid numerical artifacts that can cloud analysis. Simulation-driven analyses can only be validated by careful experiments. In this perspectives piece, we evaluate a current, widespread model of matrix metalloproteinase-driven tissue degradation during cancer invasion to illustrate that integrative computational oncology may not realize its fullest potential if either of these critical steps is neglected.